Enlivening the Effect of Tourists' Knowledge and Involvement on Malaysian Heritage Food (MHF) Towards Food Tourism Image in Malaysia - Siti Radhiah Omar; Shahrim Ab Karim; Siti Suriawati Isa; Siti Nazirah Omar (IGI Global, 2024)
Non-Indexed Publication